K-Pop Fanaticism and the Shift in Religious Education Values of the Zilenials Generation - Umniati, Umniati; Devita, Nindira Mei; Ahlan, Ahlan (Rausyan Fikri Journal of Islamic Studies, 2024)
This research aims to determine the influence of K-Pop fanatics on the religious education values of the Ziennial generation. One of them is seen in negligence in worship because he spends too much time watching his idols. The author explains fanaticism based on the Al-Qur'an as stated in the QS. Saba'. In this discussion, the researcher uses a phenomenological approach in qualitative research. This approach is intended to find out how research subjects interpret and respond to an experience or event that occurs. Primary data sources were obtained through searches through field research, books, articles, journals and the internet. This article produces findings that love of K-Pop has positive impacts such as becoming a more productive person, using K-Pop as a moodbooster and motivation for them, and being able to learn a new language. The influence of fanatics on the shift in religious values such as being careless in worship, being wasteful or too consumptive, dressing not in accordance with the Shari'a, speaking harshly, breaking ties and excessive hallucinations.